“It Was Me on a Good Day”: Exploring the Smart Drug Use Phenomenon in England - Vargo, Elisabeth J.; Petróczi, Andrea (Frontiers in Psychology, 2016)
The non-medical use of prescription medication for the pursuit of increasing cognitive and intellectual capacities (defined neuroenhancement) has received growing attention from the scientific community and policymakers alike. To date, limited qualitative data exist exploring the nature of the phenomenon, especially as a potentially emerging trend among university students in England. Existing American literature suggests that students believe that neuroenhancement helps the individual to maximize his/her time, consenting a suitable balance between work and leisure. Students’ motivation to experiment with neuroenhancement appears to be more in line with a need to regulate emotions surrounding study/work settings than to actually improve cognitive abilities beyond normal levels. This study aimed to qualitatively explore representations, motivations, beliefs and consumption styles of a cohort of university student users residing in England. Through snowball sampling, 13 informants were contacted and interviewed regarding their experience with neuroenhancers. Narrations were analysed and interpreted using qualitative analysis software and Grounded Theory methodology. Participants belonged to a broad variety of university courses and were predominantly habitual consumers of modafinil. Neuroenhancers were acquired either through friends or via the Internet. Motivations regarded the need to “catch up” and be on par with high achieving students. The entire cohort had previously experimented with other psychotropic substances. Synthetic compounds in particular were believed to be “gateway” drugs to using neuroenhancers. Experimentation with neuroenhancement can be seen as a self-governing strategy aimed at achieving continued focused productivity. Participants acknowledged sustainable benefits in neuroenhancement as it optimized work performance. The majority of the cohort also contemplated the possibility of using these drugs in the future once they entered the workforce. Neuroenhancing drug users express "situated morality", differentiating between using these substances for assessments (exams) or during revisions, finding only the former as an immoral conduct. In the present scenario, it appears that neuroenhancement is practiced by small numbers of students. Nonetheless, the instrumental views of psychotropic substances held by many young adults and the globalization of these practices make the normalization of neuroenhancement a plausible possibility of the future.